2020
DOI: 10.1175/jcli-d-19-0605.1
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Characteristics of Spring and Summer Onset El Niño Events

Abstract: El Niño events can be classified into two categories according to the onset time: the spring (SP) El Niño with onset time from April to June and the summer (SU) El Niño with onset time from July to October. The SP El Niño is a basin-scale phenomenon and is closer to the conventional ENSO. It goes through the earlier and stronger heat build-up process, and the earlier occurrence of westerlies in the equatorial Pacific, which can partly explain its earlier onset time. For SU El Niño, in contrast, the anomalous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…A mixed‐layer heat budget analysis is conducted to diagnose how the oceanic dynamical processes behave during ENSO events under the biased equatorial Pacific circulation system. In general, the TH and ZA are two dominant dynamics related to the recharge/discharge mechanism (Jin & An, 1999) that positively contribute to the mixed layer temperature anomalies during the El Niño development (Chen et al., 2016; Kug et al., 2009, 2010; Xu et al., 2020). Following the heat budget equation from Ren and Jin (2013), the TH and ZA terms can be respectively expressed as normalTnormalH=truewTsubH $\mathrm{T}\mathrm{H}=\overline{w}\frac{{T}_{\mathrm{s}\mathrm{u}\mathrm{b}}^{\prime }}{H}$ normalZnormalA=utrueTx $\mathrm{Z}\mathrm{A}=-{u}^{\prime }\frac{\partial \overline{T}}{\partial x}$ where the overbar and prime denote the climatology and anomaly.…”
Section: Resultsmentioning
confidence: 99%
“…A mixed‐layer heat budget analysis is conducted to diagnose how the oceanic dynamical processes behave during ENSO events under the biased equatorial Pacific circulation system. In general, the TH and ZA are two dominant dynamics related to the recharge/discharge mechanism (Jin & An, 1999) that positively contribute to the mixed layer temperature anomalies during the El Niño development (Chen et al., 2016; Kug et al., 2009, 2010; Xu et al., 2020). Following the heat budget equation from Ren and Jin (2013), the TH and ZA terms can be respectively expressed as normalTnormalH=truewTsubH $\mathrm{T}\mathrm{H}=\overline{w}\frac{{T}_{\mathrm{s}\mathrm{u}\mathrm{b}}^{\prime }}{H}$ normalZnormalA=utrueTx $\mathrm{Z}\mathrm{A}=-{u}^{\prime }\frac{\partial \overline{T}}{\partial x}$ where the overbar and prime denote the climatology and anomaly.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it is highly correlated with the Southern Oscillation index (SOI). Hence, we follow the definitions of Xu and Chan (2001) and Xu et al (2020) to define an El Niño event as a Spring (SP) or Summer (SU) type. When the Niño-3.4 index first exceeds 0.5 C and persists for 5 months, the first month is defined as the onset time of the El Niño events.…”
Section: Methodsmentioning
confidence: 99%
“…Many previous studies have also suggested that it has large variability on El Niño time scales, which is important in the changes in the rising branch of the Walker circulation over the WNP (Wang, 1995; Xu and Chan, 2001; Horii and Hanawa, 2004; Zhao and Wang, 2016, 2019; Wang et al . 2018; Xu et al ., 2020). At the same time, it is highly correlated with the Southern Oscillation index (SOI).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations